Phase function encoding of diffractive structures - Schilling, Andreas; Herzig, Hans-Peter (My University, 2000)
We analyzed the direct sampling (DS) method for diffractive lens encoding, using exact electromagnetic diffraction theory. In addition to previously published research [Pure Appl. Opt. 7, 565 (1998)] we present what we believe to be new results for TM polarization. We found that the validity of the scalar-based DS method is even more extended for TM than for TE polarization. Additionally, we fabricated and characterized DS-encoded blazed gratings and found good agreement between the experimental and theoretical diffraction efficiencies. We analyzed quantitatively the influence of the encoding schemes DS and analytic quantization (AQ) on the quality of the focal spot. We also investigated the focal spot sizes (FWHM) and the Strehl ratios of the DS- and the AQ-encoded cylindrical lenses.
Keywords: diffraction and gratings; binary optics; diffractive optics